Generation Z Visitors' Experience of Digital Technology Implementation Services at Bekasi Museum - Lucky Rohadi Nurohman; M. Fakhruddin; Corry Iriani Rochalina (Criksetra: Jurnal Pendidikan Sejarah, 2023)
Generation Z is known as a generation that has a high interest in digital things. The problem of this research, namely how the Generation Z Visitors' Experience of Digital Technology Implementation Services at Bekasi Museum. The purpose of this study is to describe Generation Z Visitors' Experience of Digital Technology Implementation Services at Bekasi Museum. The concept of visitor experience used is Memorable Tourism Experiences according to Kim, Ritchie, and McCormick which includes Hedonism, Novelty, Local Culture, Refreshment, Meaningfulness, Involvement, and Knowledge. The research method used is descriptive with survey techniques through the distribution of questionnaires equipped with interviews, observations, and documentation. The population in this study were generation Z visitors who visited the Bekasi Museum. As for the number of respondents, as many as 60 people obtained by using incidental sampling techniques. The results showed that generation Z visitors had memorable tourism experiences with the Digital Technology Implementation Services at Bekasi Museum. This is based on visitor experience variable data which obtains a percentage of 89,29%.